1987
DOI: 10.1148/radiology.162.2.3797670
|View full text |Cite
|
Sign up to set email alerts
|

MR imaging of the knee. Part I. Traumatic disorders.

Abstract: One hundred thirty patients with a diversity of knee joint injuries were evaluated with a high-resolution magnetic resonance (MR) imaging technique. The authors report the accuracy of this technique in the evaluation of 105 patients with suspected meniscal tears, 26 patients with suspected cruciate ligament tears, and eight patients with suspected patellar tendon injuries. Of those menisci rated as definitely or probably torn on MR imaging, 80% were found to be torn at subsequent arthroscopy. The predictive va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
28
0

Year Published

1989
1989
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(32 citation statements)
references
References 0 publications
3
28
0
Order By: Relevance
“…A small proportion of tom 'menisci are not, however, demonstrated on MR imaging. A good correlation between clinical outcome and MR appearances of normal menisci or low grade changes has been reported (34). In one study already mentioned (37), of 103 consecutive patients with knee injury that otherwise justified diagnostic arthroscopy, 59 were treated conservatively on the basis of MR findings.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…A small proportion of tom 'menisci are not, however, demonstrated on MR imaging. A good correlation between clinical outcome and MR appearances of normal menisci or low grade changes has been reported (34). In one study already mentioned (37), of 103 consecutive patients with knee injury that otherwise justified diagnostic arthroscopy, 59 were treated conservatively on the basis of MR findings.…”
Section: Discussionmentioning
confidence: 90%
“…MR images seem to possess a high ability to predict the presence of lesions remediable by arthroscopic surgeryIn one of the double-blinded studies (41) it was concluded that if the decision to perform arthroscopy had been based on the MR result rather than on the clinical judgement then 29% of the arthroscopies would have been avoided without overlooking any mechanical lesion treatable by arthroscopy. As mentioned earlier, at least 2 studies (34,37) have shown that when it comes to meniscal tears, MR images have a high ability to predict the clinical outcome and reduce the number of negative arthroscopies. If, on the basis of clinical findings and an MR examination, arthroscopy has been considered unnecessary, an unsatisfactory clinical course should evoke suspicion of a lesion not revealed by MR investigation.…”
Section: Discussionmentioning
confidence: 99%
“…for noninvasive detection of me niscal tears [1][2][3][4]. Furthermore, the diagnostic criteriafor a discoid meniscus with MR imag ing have been firmly established [5†"8].…”
Section: R Imaging Has Been Shown To Be a Sensitive And Specific Tementioning
confidence: 99%
“…1, 2 Stone et al 3 developed & evaluated a MRI technique to measure volume of menisci in 1994. Reicher et al 4 began a revolution in knee diagnosis in 1985 with MRI.…”
Section: Introductionmentioning
confidence: 99%